2018
DOI: 10.18632/oncotarget.24205
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124 aggravates failing hearts by suppressing CD151-facilitated angiogenesis in heart

Abstract: Heart failure (HF) is the final common pathway of various cardiovascular diseases. Although it is well documented that reduction of cardiac angiogenesis contributes to the progression from adaptive cardiac hypertrophy to HF, the molecular mechanisms remain unknown. In the present study, we found that cardiac expression of miR-124 was increased in patients and mice with HF. Recombinant adeno-associated virus (rAAV)-mediated miR-124 over-expression aggravated angiotensin II (Ang II) infusion-induced cardiac dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…A study by Zhao et al, has shown that miR-124 can inhibit viability, promote apoptosis, and impair migration in human endothelial cells [25]. The miR-124 targets are key pro-survival genes, including SphK1 (sphingosine kinase1) [26,27] CDK6, ROCK1 [20][21][22][23], and STAT3 (signal transducers and activators of transcription 3) [28].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zhao et al, has shown that miR-124 can inhibit viability, promote apoptosis, and impair migration in human endothelial cells [25]. The miR-124 targets are key pro-survival genes, including SphK1 (sphingosine kinase1) [26,27] CDK6, ROCK1 [20][21][22][23], and STAT3 (signal transducers and activators of transcription 3) [28].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124-3p was identified by us as regulating the highest number of genes in hiPSC-CMs. Literature data show its aggravating role in failing hearts by suppressing CD151-facilitated angiogenesis in the heart [110]. miR-124-3p dysregulates NSC maintenance through repression of the transferrin receptor (TFRC) in Zika virus infection [111].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miR-133b has roles both in the brain and the heart. Another example is miR-124, along with miR-124-5p and miR-124-3p, which are known for their protective roles in cardiac injury, angiogenesis, and other heart diseases [180,181]. In addition, miR-124-3p is an efficient prognostication tool for neurological outcome and survival in patients post-cardiac arrest [59].…”
Section: Non-coding Rnas In the Brain-heart Axis In Pdmentioning
confidence: 99%